2018
DOI: 10.1007/s41230-018-8105-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on mechanical properties of aluminium 7075 - boron carbide - coconut shell fly ash reinforced hybrid metal matrix composites

Abstract: A luminium matrix composites (AMC) are used in advanced engineering applications such as automotive and aerospace industries and lightweight high strength applications to fulfil the emerging industrial requirements due to their good mechanical and tribological properties. Al7075 reinforced with B 4 C composites produced by casting route showed the improvement in hardness and tensile properties [1-3]. Zhang et al. [4] reported that aluminium fly ash composites were manufactured by liquid reactive sintering powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(28 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…It seems that the addition of a certain amount weight percentage of reinforcements (5-15 wt%) B 4 C entails a higher yield strength (~ 136 MPa) at the expenses of lower tensile strength in respect to base material AA6061. The results agree with [22], where by an increase in B 4 C they obtained a lower tensile strength for 15 wt% B 4 C. Table 1 shows the value of the break load, ultimate tensile strength (UTS), % of elongation, and yield stress for the three samples and a base metal. It is observed that breaking load, UTS, and % of elongation are reduced in a gradual manner while increasing wt.…”
Section: Tensile Behavioursupporting
confidence: 83%
“…It seems that the addition of a certain amount weight percentage of reinforcements (5-15 wt%) B 4 C entails a higher yield strength (~ 136 MPa) at the expenses of lower tensile strength in respect to base material AA6061. The results agree with [22], where by an increase in B 4 C they obtained a lower tensile strength for 15 wt% B 4 C. Table 1 shows the value of the break load, ultimate tensile strength (UTS), % of elongation, and yield stress for the three samples and a base metal. It is observed that breaking load, UTS, and % of elongation are reduced in a gradual manner while increasing wt.…”
Section: Tensile Behavioursupporting
confidence: 83%
“…The reinforcement phase is evenly distributed or embedded into the matrix phase [6]. The matrix is defined as a metal alloy in the productivity of the composite.…”
Section: Composite Materialsmentioning
confidence: 99%
“…Aluminium 7075 is an aluminium alloy, in which grades usually used in production of 7075-T6, 7075-T651. The chemical composition and properties of Al7075 is shown in Table no 1 & 2 respectively [6]. Al7075 are often preferred in transport, marine, automotive and aviation applications, because of its high strength-to-weight ratio.…”
Section: Al7075 Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum matrix composite has gain importance than Mg because of ease of fabrication [3]. AA6061 series possess moderate strength with lightweight and it is widely used for structural, aviation and automobile applications [4].…”
Section: Introductionmentioning
confidence: 99%